ANTIBIOGRAM STUDIES OF SALMONELLA ENTERITIDIS PHAGE TYPE 4 ISOLATES FROM POULTRY AND MEAT - Shaheen, Nusrat; Fatima, Naheed; Sajid, Saraj -ud-Din; Gandapur, Abdus Salam Khan (Journal of Ayub Medical College Abbottabad, 2004)
Background: Human infection with Salmonella enteritidis phage type 4 has increased worldwide since last decade and has been shown to be related mainly with the consumption of poultry meat and eggs. The public health significance and economic importance of this serovar underscores the need to generate base line data on the antimicrobial susceptibilities and protein profile of indigenous S. enteritidis. This study was performed to investigate the antimicrobial susceptibilities of S. enteritidis PhageType4 isolates from poultry and meat. Method: This study was carried out in the department of biological sciences Quaid-i-Azam University Islamabad during 1998-2000. A total of nineteen quinolone sensitive isolates of S. enteritidis from poultry meat and eggs collected during1994-1998 were characterized. The isolates were serotyped and phage typed at federal institute of consumer Health and Veterinary Medicine, Wernigerode Germany. Antimicrobial susceptibility tests were performed in accordance to the method of Bauer et al. (1966). Results: The results of the standard disc diffusion test showed 100% resistance against bacitracin, erythromycin and novobiocin. All (100%) isolates were highly sensitive to chloramphenicol. The results of minimum inhibitory concentration (MICs) tests using serial dilution of antimicrobial drugs revealed that 100% of the isolates were resistant against bacitracin, erythromycin and novobiocin at various levels of concentrations. Kanamycin, streptomycin and spectinomycin, all had very poor activity against serovar Enteritidis. Conclusion: These findings suggest the limited therapeutic potential and low typability of this serovar. Key Words: Antibiogram, Salmonella Enteritidis, Phage Type 4.